Antimicrobial Efficacy of Green Synthesized Nanosilver with Entrapped Cinnamaldehyde against Multi-Drug-Resistant Enteroaggregative Escherichia coli in Galleria mellonella - Vemula Prasastha Ram; Jyothsna Yasur; Padikkamannil Abishad; Varsha Unni; Diksha Purushottam Gourkhede; Maria Anto Dani Nishanth; Pollumahanti Niveditha; Jess Vergis; Satya Veer Singh Malik; Byrappa Kullaiah; Nitin Vasantrao Kurkure; Chatragadda Ramesh; et al. (MDPI AG, 2022)
The global emergence of antimicrobial resistance (AMR) needs no emphasis. In this study, the in vitro stability, safety, and antimicrobial efficacy of nanosilver-entrapped cinnamaldehyde (AgC) against multi-drug-resistant (MDR) strains of enteroaggregative Escherichia coli (EAEC) were investigated. Further, the in vivo antibacterial efficacy of AgC against MDR-EAEC was also assessed in Galleria mellonella larval model. In brief, UV-Vis and Fourier transform infrared (FTIR) spectroscopy confirmed effective entrapment of cinnamaldehyde with nanosilver, and the loading efficiency was estimated to be 29.50 ± 0.56%. The AgC was of crystalline form as determined by the X-ray diffractogram with a mono-dispersed spherical morphology of 9.243 ± 1.83 nm in electron microscopy. AgC exhibited a minimum inhibitory concentration (MIC) of 0.008-0.016 mg/mL and a minimum bactericidal concentration (MBC) of 0.008-0.032 mg/mL against MDR- EAEC strains. Furthermore, AgC was stable (high-end temperatures, proteases, cationic salts, pH, and host sera) and tested safe for sheep erythrocytes as well as secondary cell lines (RAW 264.7 and HEp-2) with no negative effects on the commensal gut lactobacilli. in vitro, time-kill assays revealed that MBC levels of AgC could eliminate MDR-EAEC infection in 120 min. In G. mellonella larvae, AgC (MBC values) increased survival, decreased MDR-EAEC counts (p < 0.001), had an enhanced immunomodulatory effect, and was tested safe to the host. These findings infer that entrapment enhanced the efficacy of cinnamaldehyde and AgNPs, overcoming their limitations when used individually, indicating AgC as a promising alternative antimicrobial candidate. However, further investigation in appropriate animal models is required to declare its application against MDR pathogens.